GLYPHOSATE TOXICITY STUDY IN CABBAGE AND RADISH GERMINATION - Villa, F. B.; Monteiro, J. O. F.; Godoy, G. B.; Souza, D. S. S.; Ramos, J. L.; Dias, A. B.; Portela, A. L. R.; Cristiano, G. A.; Godoi, I. R. G.; Gabriel, L.; et al. (Revista Brasileira de Engenharia de Biossistemas, 2019)
This work aimed to evaluate the toxic effects of glyphosate (N- (phosphonomethyl) -glycine), a herbicide widely used in Brazilian agriculture, as a stressor, through a methodology of evaluation of chronic and acute toxicity in cabbage (Brassica oleracea L.) and radish (Raphanus sativus L.) seeds. The chosen methodology allowed the analysis of the parameters NOEC (Not Observable Effect Concentration), LOEC (Lowest Observable Effect Concentration) and EC50 (Effective Concentration) for each species. For radish, it was observed that NOEC appeared in 1 mg L-1 stressor, LOEC at 2 mg L-1 and EC50 at approximately 7 mg L-1. For cabbage, NOEC appeared at 16 mg L-1, LOEC at 18 mg L-1 and EC50 between 14 e 15 mgL-1. It was possible to get, through the study, a high pH control (7.0 for radish and 7.5 for cabbage), high sensitivity and low cost compared to other toxicity tests.